Forest Products Annual Market Review 2016-2017 - United Nations (United Nations, 2018)
This publication provides a comprehensive analysis of markets in the UNECE region and reports on the main market influences outside the UNECE region. It covers the range of products from the forest to the end-user: from roundwood and primary processed products to value-added and housing. Statistics-based chapters analyse the markets for wood raw materials, sawn softwood, sawn hardwood, wood-based panels, paper, paperboard and woodpulp. Other chapters analyse policies, trade barriers affecting forest products, and markets for wood energy. The Review highlights the role of sustainable forest products in international markets. It also analyses the effects of the current economic situation on forest products markets.